Laboratory and febrile features after joint surgery in patients with rheumatoid arthritis treated with tocilizumab. Issue 5 (2nd June 2008) - Hirao, M; Hashimoto, J; Tsuboi, H; Nampei, A; Nakahara, H; Yoshio, N; Mima, T; Yoshikawa, H; Nishimoto, N
Abstract : Objectives: To understand the acute phase responses to surgical intervention in patients with rheumatoid arthritis (RA) treated with the anti-interleukin (IL)6 receptor antibody, tocilizumab. Methods: In a retrospective 1:1 pair-matched case-control study, 22 tocilizumab-treated RA cases and 22 cases treated with conventional disease-modifying antirheumatic drugs (DMARDs) and matched for type of surgery, age and sex were evaluated for body temperature every day, and blood C-reactive protein (CRP) levels and white blood cell (WBC), neutrophil and lymphocyte counts on days −1, 1, 3 and weeks 1 and 2 after joint surgery. Safety issues were also monitored. Results: No complications of infection or delay of wound healing occurred in either patient group. Tocilizumab partially, but significantly, suppressed the increase in body temperature on postoperative days 1 and 2, compared with DMARDs (average (SD) maximum increase in temperature was 0.45 (0.1)°C in the tocilizumab group and 0.78 (0.1)°C in the DMARD group; p<0.01). Tocilizumab completely suppressed the increase in CRP after surgery, whereas all cases treated with DMARDs showed a significant increase of CRP at postoperative day 1 (5.5 (0.6) mg/dl; p<0.001). WBC, neutrophil and lymphocyte counts showed no remarkable change after surgery, and there was no significant difference in any cell counts between the patient groups. Conclusions: Within this small number of cases, safe operations on patients were performed during tocilizumab treatment. Tocilizumab suppressed fever and increase of CRP after surgery, whereas there was no influence on the transition in number of leukocytes. This characteristic postoperative response should be considered during tocilizumab treatment.